COMPARATIVE ANALYSIS OF TEMPERATURE EFFECTS ON FOUR KINDS OF FLEXURE HINGES - HU JunFeng; HAO YaZhou; XU GuiYang (Jixie qiangdu)
In order to reduce the temperature effects on compliant mechanisms,the comparative analysis of temperature effects on four kinds of typical flexure hinge with straight-beam,circular,elliptic and parabolic section is carried out,so that we can choose reasonablely the flexure hinge used to design compliant mechanisms. The flexure hinge is diviede into two variable cross-section beam elements,and the initial strain caused by temperature change is accounted into. The principle of minimum potential energy is applied to derive the thermal load vector and stiffness matrix of four kinds flexure hinge,and the mass matrix is obstained by employing Lagrange equation. And the mechanical model of the flexure hinges is obtained. The comparative analysis of the precision,thermal stress and thermal vibration of the compliant four-link mechanism is carried out based on the finite element model of the flexure hinge. The analysis results showed that the thermal errors of circular hinge is largest,and parabolic one,elliptic and straight-beam is smallest; The sequence of thermal stress from large to small is circular,elliptic,parabolic and straight-beam flexure hinge; The thermal vibration resonant frequency of the straight-beam hinge is minimum,the circular and elliptic one is second,parabolic is maximum,and it illustrated that the straight-beam hinge is more sussceptible to temperature changes. But the amplitude of the parabolic hinge at the resonant frequecy is maximum,and the thermal vibration is more larger.